Forget Kathmandu : an elegy for democracy - Thapa, Manjushree (New Delhi ; New York : Penguin, Viking, 2005)
Author's impression on the political conditions in Nepal post 2001 while travelling through the affected areas of political strife.
ARC
Keywords: Thapa, Manjushree -- Travel -- Nepal; Authors, Nepali -- Travel; Nepal -- Politics and government -- 1990-; Nepal -- Description and travel